Study and Design of Picohydro Power Plant for Low-Head and Low-Flow Application - HAMDANI, DENY; EDYPOERWA, MUGNI LABIB (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
The global energy transition trend has driven the utilization of renewable energy from the surrounding environment, one of which is the irrigation water flow. Picohydro Power Plant (PLTPH) offers a solution to harvest kinetic and potential energy from water flow with low discharge and head. This study designed a PLTPH based on a classic water wheel equipped with an impulsive nozzle, a gradual intake pipe, a booster converter, an MPPT device, and a battery to ensure optimal and stable power output. With a water flow discharge of 0.4 m/s and a head of 80 cm, the PLTPH can generate up to 1,100 W, demonstrating the effectiveness of this technology in supporting energy transition and energy utilization in remote areas.